2022
DOI: 10.3390/pathogens12010004
|View full text |Cite
|
Sign up to set email alerts
|

Entomo-Virological Aedes aegypti Surveillance Applied for Prediction of Dengue Transmission: A Spatio-Temporal Modeling Study

Abstract: Currently, DENV transmitted primarily by Aedes aegypti affects approximately one in three people annually. The spatio-temporal heterogeneity of vector infestation and the intensity of arbovirus transmission require surveillance capable of predicting an outbreak. In this work, we used data from 4 years of reported dengue cases and entomological indicators of adult Aedes collected from approximately 3500 traps installed in the city of Foz do Iguaçu, Brazil, to evaluate the spatial and temporal association betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…However, further investigations demonstrated the inability of the indicators to predict space-time occurrence with T A B L E 2 Akaike information criteria results ranking the most parsimonious a priori scenario models (descending order) that predict the incidence of dengue cases based on surveys of Aedes aegypti mosquitoes at Geographic Unity Scale, Foz do Iguaçu, Brazil. a geographic precision at sub-municipal levels with spatial units of an average of 1500 properties [34]. The TPI and ADI were estimated after inspecting a total of approximately 3500 Adultraps distributed over the city in a ratio of one every 25 premises [32].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, further investigations demonstrated the inability of the indicators to predict space-time occurrence with T A B L E 2 Akaike information criteria results ranking the most parsimonious a priori scenario models (descending order) that predict the incidence of dengue cases based on surveys of Aedes aegypti mosquitoes at Geographic Unity Scale, Foz do Iguaçu, Brazil. a geographic precision at sub-municipal levels with spatial units of an average of 1500 properties [34]. The TPI and ADI were estimated after inspecting a total of approximately 3500 Adultraps distributed over the city in a ratio of one every 25 premises [32].…”
Section: Discussionmentioning
confidence: 99%
“…aegypti infestation rates in the adult stage, highlighting both TPI and ADI are capable to predict dengue outbreaks 4 weeks in advance. However, further investigations demonstrated the inability of the indicators to predict space–time occurrence with geographic precision at sub‐municipal levels with spatial units of an average of 1500 properties [34]. The TPI and ADI were estimated after inspecting a total of approximately 3500 Adultraps distributed over the city in a ratio of one every 25 premises [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Uncontrolled urbanization, rising temperatures, and a lack of effective long-term vector control tools have aided Aedes aegypti adaptation to urban environments throughout the world. [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Claver et al [ 8 ] reported relatively modest vector competence for Aedes aegypti in Vientiane, Lao PDR, to transmit the Asian and ECSA-IOL lineages of chikungunya virus, which may be influenced by the longevity and density of female mosquitoes. Leandro et al [ 9 ] evaluated the spatial and temporal association between vector infestation and the occurrence of dengue cases and reported a dynamic pattern indicating significant risks in certain areas of Foz do Iguaçu, Brazil, based on the entomological–virological index, while entomological indices were not effective in measuring dengue risk. Another study tested the efficacy of modifications to sewerage structures as an alternative to the use of biocides to prevent the breeding of Culex pipiens and Aedes albopictus in Barcelona, Spain [ 10 ].…”
mentioning
confidence: 99%